Fluctuating asymmetry in ecological and environmental research: Quo vadis? - Kozlov, Mikhail V. (Wiley, 2025)
Májeková et al. (2024) demonstrated that leaf fluctuating asymmetry (FA) is not a reliable indicator of stress. I broaden the perspective on the findings by these authors.
High prevalence of confirmation bias could explain why as much as 39% of 131 unique entries (plant species × stress type) in the database of published studies compiled by these authors showed the significant increase in FA with stress.
The use of blind methods should be considered obligatory for any study addressing environmental or genetic impacts on FA.
Both data and conclusions from FA-related studies that did not report blinding should only be used when proof of negligible impact from confirmation bias can be provided.
It is essential that all measures taken against biases are described in each submitted manuscript, and that the need to check for these requirements is included in instructions for reviewers.